Amino acid composition of nanofibrillar self-assembling peptide hydrogels affects responses of periodontal tissue cells in vitro - Koch F (Dove Medical Press, 2018)
Franziska Koch,1–3 Anne Wolff,2 Stephanie Mathes,4 Uwe Pieles,1 Sina S Saxer,1 Bernd Kreikemeyer,3 Kirsten Peters2 1Institute for Chemistry and Bioanalytics, School of Life Sciences, University of Applied Sciences and Arts Northwestern Switzerland, Muttenz, Switzerland; 2Department of Cell Biology, University Medicine Rostock, Rostock, Germany; 3Institute of Medical Microbiology, Virology and Hygiene, University Medicine Rostock, Rostock, Germany; 4Department for Chemistry and Biotechnology, Tissue Engineering, Zurich University of Applied Sciences, Wädenswil, Switzerland Background: The regeneration of tissue defects at the interface between soft and hard tissue, eg, in the periodontium, poses a challenge due to the divergent tissue requirements. A class of biomaterials that may support the regeneration at the soft-to-hard tissue interface are self-assembling peptides (SAPs), as their physicochemical and mechanical properties can be rationally designed to meet tissue requirements. Materials and methods: In this work, we investigated the effect of two single-component and two complementary β-sheet forming SAP systems on their hydrogel properties such as nanofibrillar architecture, surface charge, and protein adsorption as well as their influence on cell adhesion, morphology, growth, and differentiation. Results: We showed that these four 11-amino acid SAP (P11-SAP) hydrogels possessed physicochemical characteristics dependent on their amino acid composition that allowed variabilities in nanofibrillar network architecture, surface charge, and protein adsorption (eg, the single-component systems demonstrated an ~30% higher porosity and an almost 2-fold higher protein adsorption compared with the complementary systems). Cytocompatibility studies revealed similar results for cells cultured on the four P11-SAP hydrogels compared with cells on standard cell culture surfaces. The single-component P11-SAP systems showed a 1.7-fold increase in cell adhesion and cellular growth compared with the complementary P11-SAP systems. Moreover, significantly enhanced osteogenic differentiation of human calvarial osteoblasts was detected for the single-component P11-SAP system hydrogels compared with standard cell cultures. Conclusion: Thus, single-component system P11-SAP hydrogels can be assessed as suitable scaffolds for periodontal regeneration therapy, as they provide adjustable, extracellular matrix-mimetic nanofibrillar architecture and favorable cellular interaction with periodontal cells. Keywords: self-assembling peptides, SAPs, P11-SAP hydrogels, surface charge, protein adsorption, cell proliferation, osteogenic differentiation, periodontal tissue regeneration